PERCEPTION AND OBSTACLES OF COLLEGE STUDENTS IN WRITING - Adiwijaya, Pande Agus; Purnami, Ni Made Ayu; S Arsana, I Wayan (Institut Hindu Dharma Negeri Denpasar, 2019)
This is a descriptive qualitative research which aimed at finding the perception and obstacles of college students in writing. The subject of this research was all of students in English Education Department of STKIP Suar Bangli in academic year 2018/2019. There were three instruments used in this research, namely questionnaire, interview and documentation. From the data analysis it was found that students of English Education Department considered writing was important for them and considered as the second most important skill after speaking. Teaching writing skill should be taught through the process of writing (drafting, writing and revising) in relax and fun situation with many practices. The evaluation of writing should also provide feedbacks for their writing improvement. The most challenging obstacle that should be solved by the students was finding ideas. The students also proposed some reasons that may trigger them to write such as having idea/inspiration, having assignment, being in a good mood, there is time allocation for writing, having motivation, and being in supportive situation and condition. It is also suggested to teach writing skill by using project-based learning through proper process of writing starting from pre-writing, drafting, writing, revision and editing. The evaluation was also in form of portfolio assessment.